Intelligent techniques in recommendation systems contextual advancements and new methods - Dehuri, Satchidananda 1976-; Patra, Manas Ranjan; Misra, Bijan Bihari; Jagadev, Alok Kumar (Premier reference source, 2013)
"This book is a comprehensive collection of research on the latest advancements of intelligence techniques and their application to recommendation systems and how they could improve this field of study" - Provided by publisher